2022
DOI: 10.1136/gutjnl-2022-327005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted intervention to achieve waste reduction in gastrointestinal endoscopy

Abstract: ObjectiveEndoscopy is healthcare’s third largest generator of medical waste in hospitals. This prospective study aimed to measure a single unit’s waste carbon footprint and perform a pioneer intervention towards a more sustainable endoscopy practice. The relation of regulated medical waste (RMW; material fully contaminated with blood or body fluids or containing infectious agents) versus landfill waste (non-recyclable material not fully contaminated) may play a critical role.DesignIn a four-stage prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…In the surgical field, laparoscopic hysterectomy, cataract surgery, neurosurgery and skin cancer surgery produce 12.0, 3.0, 8.9 and 2.6 kg of waste, respectively 12 16–18. In GI endoscopy, several publications have estimated the total waste of a single endoscopy procedure (0.5–2.1 kg) 7 8 19. In our study, only taking into account biopsy forceps, polypectomy snares and haemostatic clips, total BMW per procedure was approximately 0.05 kg.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In the surgical field, laparoscopic hysterectomy, cataract surgery, neurosurgery and skin cancer surgery produce 12.0, 3.0, 8.9 and 2.6 kg of waste, respectively 12 16–18. In GI endoscopy, several publications have estimated the total waste of a single endoscopy procedure (0.5–2.1 kg) 7 8 19. In our study, only taking into account biopsy forceps, polypectomy snares and haemostatic clips, total BMW per procedure was approximately 0.05 kg.…”
Section: Discussionmentioning
confidence: 60%
“…In our study, only taking into account biopsy forceps, polypectomy snares and haemostatic clips, total BMW per procedure was approximately 0.05 kg. Cunha Neves et al demonstrated that after an educational staff intervention, it was possible to reduce general landfill waste and BMW, and thus minimise waste carbon footprint 8. They achieved a reduction of total waste and BMW by 12.9% and 41.4%, respectively, and a total decrease of carbon footprint by 31.6% 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, poor medical waste management has harmful economic and ecological impacts. Educational measures regarding recycling and appropriate waste management have been demonstrated to be efficient and do not compromise productivity [17]. Also, increasing the proportion of effectively recycled waste will decrease the carbon footprint of endoscopic units and the costs associated with waste management as recycled items can receive economic valorization.…”
Section: Discussionmentioning
confidence: 99%